A New Method for the Analysis of Bacterial Endotoxins in Ultrapure Paraffin Oil. (9th March 2014) - Chen, Dandan
Abstract : The paper demonstrates the feasibility of the gel-clot method for the analysis of bacterial endotoxins in water extracts of ultrapure paraffin oil which is a water insoluble oily medical device. Because ultrapure paraffin oil is water insoluble oily liquid, the ultrapure paraffin oil (10 mL) was shaken with 10 mL water for 15 minutes at 2000 rpm, the endotoxin present was extracted to the aqueous phase without interference inhibition/enhancement of the product, the recovery of the endotoxin added to the ultrapure paraffin oil was determined. A validation study confirmed that endotoxins present in ultrapure paraffin oil which is water insoluble liquid medical device pass over into the aqueous phase at concentrations of 20, 10, and 5 EU/mL with recoveries of 94.2% to 111%. So the conclusion is that the gel-clot test is suitable for detecting bacterial endotoxins in ultrapure paraffin oil which is a water insoluble oily medical device.